2014
DOI: 10.1177/1934578x1400901005
|View full text |Cite
|
Sign up to set email alerts
|

One-pot Synthesis of Hollongdione from Dipterocarpol

Abstract: A one-pot synthesis of a hybrid triterpenoid-steroid molecule, hollongdione (22,23,24,25,26,27-hexanordammar-3,20-dion), was achieved in a yield of 89%, based on the selective dehydration of dipterocarpol following ozonolysis. The structure of hollongdione was confirmed by X-ray analysis for the first time. Dammar-20(22),24(25)-dien inhibited the growth of Mycobacterium tuberculosis (strain H37Rv) in vitro with a MIC of 50 µg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The signals of aromatic carbons and their corresponding protons were observed at  C 111.31-160.44 ppm and  H 6.76-7.54ppm. Generally, the spectral data for the rings B, C, and D and side chain of compounds 5-3 are in complete agreement with those reported for dammaranes [7,14,[25][26].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The signals of aromatic carbons and their corresponding protons were observed at  C 111.31-160.44 ppm and  H 6.76-7.54ppm. Generally, the spectral data for the rings B, C, and D and side chain of compounds 5-3 are in complete agreement with those reported for dammaranes [7,14,[25][26].…”
supporting
confidence: 86%
“…Dipterocarpol [(20S)-20-hydroxydammar-24-en-3-one] is the major metabolite of oleoresins of trees Dipterocarpus species [2]. Such chemical transformations of dipterocarpol as preparation of Nvinylpyrrolidone, γ-lactone, alkoxytetrahydrofuran, hydroxy-, epoxy-, oximino-,1,2,4-trioxolane,heterocyclic, 2-cyanoethoxy-, tetrazole as well as hybrid triterpenoid-steroid and derivatives were described [3][4][5][6][7][8][9]. It was demonstrated that dammarane triterpenoids possess anticancer [10], antiviral [11][12][13], immunostimulating [14] and anti-inflammatory [15] activities.…”
mentioning
confidence: 99%
“…3H, s), 1.36 (3H, s), 0.97 (3H, s), 0.93 (3H, s), 0.90 (6H, brs). 13 27,30 This compound was used as the starting material for the synthesis of the oxime and lactone derivatives.…”
Section: Experimentationmentioning
confidence: 99%
“…2). It was reported that dipterocarpol and its derivatives exhibit antituberculosis, 27 antimicrobial, 28 hepatoprotective, 29 and cytotoxic activity. 30 In this work, two different approaches to modify the structure of dipterocarpol are proposed based on their advantages reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our investigation program of the plant triterpenoids pharmacological potency (Kazakova et al 2010a, b;Kazakov et al, 2011;Kazakova et al 2011a, d;Kazakov et al, 2012;Kazakova et al 2013;Smirnova et al 2014Smirnova et al , 2015Tret'yakova et al, 2014;Yamansarov et al, 2015), we present here the synthesis of triterpenoids bearing cyanoethyl and aminopropoxy chains at the C-28 and C-3 or C-28 positions and their in vitro and in vivo anticancer activity. Fig.…”
Section: Introductionmentioning
confidence: 99%